Comparison of creatine monohydrate and carbohydrate supplementation on repeated jump height performance - Koenig, C. A.; Benardot, D.; Cody, M.; Thompson, W. R. (The Journal of Strength and Conditioning Research, 2008)
Creatine monohydrate (CrMH) supplementation aids the ability to maintain performance during repeated bouts of high-intensity exercise, including jump performance. However, carbohydrate supplementation may also provide similar benefits and is less expensive. This study compared the effects of an energy-free placebo, 2 different caloric concentrations of carbohydrate drinks, and a CrMH supplement on repeated jump heights. Sixty active males (mean age, 22 ± 3.2 years) performed 2 sets of countermovement static jump height tests (10 jumps over 60 seconds) separated by 5 days to determine the differential effects of the placebo, carbohydrate, and CrMH on jump height sustainability over 10 jumps. Subjects were randomly assigned to groups (15 subjects per group) to receive daily doses (×5 days) of carbohydrate drinks containing 100 or 250 kilocalories (kcal), a 25-g CrMH supplement, or an energy-free placebo. After 5 days, the CrMH group experienced a significant weight gain (+1.52; ±0.89 kg, p < 0.01), while the other groups did not. The 2 levels of carbohydrate and CrMH supplements were all significantly better at sustaining jump height than the energy-free placebo over the final 3-4 jumps. The 250-kcal carbohydrate-supplemented group experienced a level of benefit (p < 0.01) that was at least equal to that of the CrMH group (p < 0.05), suggesting that the higher dose of carbohydrate was as effective as CrMH in maintaining repeated bouts of high-intensity activity as measured by repeated static jumps. Given the equivalent performance improvement and the absence of weight gain, the carbohydrate supplementation could be considered the preferred option for weight-conscious power athletes involved in activities that require repeated- motion high-intensity activities.